Understanding Myanmar and the Way Forward for Legal Education: From Rote Learning to Community Engagement Through Clinical Legal Education. (July 2020) - Ross, Nicholas; Ardussi, Carly; Tushaus, David; Win, Soe Thiri; Lwin, Zwe Pyae Sone
The aim of this article is to use a community needs assessment to teach law students knowledge, skills and values while identifying the areas of greatest need for access to justice services in the community. To begin, the international team of US and Myanmar law faculty and students researched literature on the country of Myanmar and various issues facing Myanmar's citizens and its legal education system. We also had a team from Missouri Western State University on the ground in Myanmar working with the international non-governmental organization (NGO) BABSEACLE (formerly, B ridgesA crossB ordersS outhE astA siaC linicalL egalE ducation) to work with faculty and students at the Department of Law, Taunggyi. The team conducted a community needs assessment (CNA) on legal needs in Taunggyi, Myanmar, to better understand community teaching needs. BABSEACLE provides law schools with the tools and opportunities to expand clinical legal education (CLE). The team in Myanmar from Missouri Western State University consisted of Professor David Tushaus and two undergraduate students, Britane Hubbard and Kaylee Sharp, who had the opportunity to teach CLE in English to law students at Taunggyi University. Professor Tushaus served as an international clinician in residence (ICIR). BABSEACLE, operating in Myanmar since 2013, has successfully used ICIRs to introduce and strengthen CLE, by embedding experienced law professors and practitioners at local universities to serve as mentors to neophyte clinical faculty. 5